ANALISIS PENGARUH KEMAMPUAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA PADA DINAS PENDIDIKAN DAN KEBUDAYAAN DAERAH PROVINSI SULAWESI BARAT - Mukhsin Yahya (Jurnal Humaniora & Sosial Sains, 2024)
The study aims to analyze the Influence of Work Ability and Work Environment on Employee Performance Through Work Motivation at the Regional Education and Culture Office of West Sulawesi Province. This study is classified as a survey study with a quantitative approach. The population in this study was 167 employees with a sample technique of saturated samples (Census). Data were collected using a questionnaire with a Likert scale as an alternative answer choice. The data analysis technique used in testing the hypothesis was path analysis with the help of SPSS and Amos. The results of the study showed that employee work ability did not have a positive and insignificant effect on employee performance, while a conducive work environment had a positive and significant effect on employee performance. Work ability also did not significantly affect work motivation, but a good work environment contributed to increasing employee work motivation. In addition, work motivation directly affected employee performance, highlighting the importance of motivational factors in achieving optimal results. This study provides important insights into the internal and external dynamics that affect employee performance at the Regional Education and Culture Office of West Sulawesi Province, as well as management implications that can be applied to improve organizational effectiveness.